Effect of Ni content on the diffusion-controlled growth of the product phases in the Cu(Ni)–Sn system. Issue 1 (2nd January 2016) - Baheti, Varun A.; Islam, Sarfaraj; Kumar, Praveen; Ravi, Raju; Narayanan, Ramesh; Hongqun, Dong; Vuorinen, Vesa; Laurila, Tomi; Paul, Aloke
Abstract: A strong influence of Ni content on the diffusion-controlled growth of the (Cu, Ni)3 Sn and (Cu, Ni)6 Sn5 phases by coupling different Cu(Ni) alloys with Sn in the solid state is reported. The continuous increase in the thickness ratio of (Cu, Ni)6 Sn5 to (Cu, Ni)3 Sn with the Ni content is explained by combined kinetic and thermodynamic arguments as follows: (i) The integrated interdiffusion coefficient does not change for the (Cu, Ni)3 Sn phase up to 2.5 at.% Ni and decreases drastically for 5 at.% Ni. On the other hand, there is a continuous increase in the integrated interdiffusion coefficient for (Cu, Ni)6 Sn5 as a function of increasing Ni content. (ii) With the increase in Ni content, driving forces for the diffusion of components increase for both components in both phases but at different rates. However, the magnitude of these changes alone is not large enough to explain the high difference in the observed growth rate of the product phases because of Ni addition. (iv) Kirkendall marker experiments indicate that the Cu6 Sn5 phase grows by diffusion of both Cu and Sn in the binary case. However, when Ni is added, the growth is by diffusion of Sn only. (v) Also, the observed grain refinement in the Cu6 Sn5 phase with the addition of Ni suggests that the grain boundary diffusion of Sn may have an important role in the observed changes in the growth rate.